Speech and language processing an introduction to natural language processing, computational linguistics, and speech recognition - Jurafsky,Dan, 1962- (Prentice Hall series in artificial intelligence, 2009)
For undergraduate or advanced undergraduate courses in Classical Natural Language Processing, Statistical Natural Language Processing, Speech Recognition, Computational Linguistics, and Human Language Processing. An explosion of Web-based language techniques, merging of distinct fields, availability of phone-based dialogue systems, and much more make this an exciting time in speech and language processing.